DEATH PENALTY TO DRUG TRAFFICKERS FROM THE PERSPECTIVE OF SIYĀSAH SYAR’IYYAH - Wan Husin, Wan Norhasnih (Ar Raniry : International Journal of Islamic Studies, 2016)
In Malaysia, drug abuse and drug trafficking began affecting the society seriously around the 70s and, the trend has continued unabatedly in the first decade of the new millennium. The outcomes are staggering, as it is the cause of various social ills such as murder, burglary, prostitution, and even causes family disintegration and erodes social relations. The main objective of this study is to analyze from the Islamic perspective on the death penalty based on the siyÃ„Âsah SyarÃ¢â‚¬â„¢iyyah principles since the punishment by death for drug trafficking is not an offence directly stated in the al-Quran and al-Sunnah under the hudud law. Based on textual analysis, the study finds that the death penalty meted out against drug traffickers is justified based on the severity of the act in affecting the individual involved, society and the nation.Ã‚Â